Faith and narrative - Yandell, Keith E., 1938- (Oxford University Press, 2001)
From epic to limerick, novel to anecdote, literary narratives engage and entertain us. From autobiography and biography to accounts of familial generations, narratives define communities. Myths and histories loom large in religious traditions as well. Recently, the importance of narrative to ethics and religion has become a pervasive theme in several scholarly disciplines. In the essays presented here, a distinguished roster of scholars addresses a range of issues associated with this theme, focussing especially on questions concerning narrative's contribution to knowledge.